2019
DOI: 10.1371/journal.ppat.1007801
|View full text |Cite
|
Sign up to set email alerts
|

Chromulinavorax destructans, a pathogen of microzooplankton that provides a window into the enigmatic candidate phylum Dependentiae

Abstract: Members of the major candidate phylum Dependentiae (a.k.a. TM6) are widespread across diverse environments from showerheads to peat bogs; yet, with the exception of two isolates infecting amoebae, they are only known from metagenomic data. The limited knowledge of their biology indicates that they have a long evolutionary history of parasitism. Here, we present Chromulinavorax destructans (Strain SeV1) the first isolate of this phylum to infect a representative from a widespread and ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 49 publications
(71 reference statements)
0
50
0
Order By: Relevance
“…In that same fish, we found that the SMS contained more Dependentiae (genus) and a taxa characterized as “metagenome” from the class Babeliales. Both of these taxa are possible protist endosymbionts (Pagnier et al, 2015; Yeoh et al, 2016; Deeg et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In that same fish, we found that the SMS contained more Dependentiae (genus) and a taxa characterized as “metagenome” from the class Babeliales. Both of these taxa are possible protist endosymbionts (Pagnier et al, 2015; Yeoh et al, 2016; Deeg et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…At class level this resulted in a higher similarity of the relative abundances of the prokaryotic communities of the columns (Figure 7B), with Gammaproteobacteria as the most abundant group on average. This also revealed the class Babeliae in the phylum Dependentiae, which is often found to be pathogens of diverse aquatic protists (Deeg et al, 2019), to be present throughout the inoculated columns and in the inlet end of the control column receiving untreated water ( Figure 7B) in up to 1.3% relative abundance. On the other hand, when inspecting the heatmap of the most abundant OTUs, just a few are only present in the control columns; Rhodoferax sp.…”
Section: Total Bacterial Communities In the Columnsmentioning
confidence: 85%
“…Interestingly, this showed that the class Babeliae in the phylum Dependentiae was present throughout the inoculated columns and in the inlet end of the control columns ( Figure 7B). Members of the phylum Dependentiae (previously called TM6) are often found to be pathogens of diverse aquatic protozoa (Delafont et al, 2015;Deeg et al, 2019). Though found to be only a small part of the total bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…Dependentiae is a candidate bacterial phylum that has been noted for its reduced coding potential, including a depletion in electron transport chain components (McLean et al, 2013;Yeoh et al, 2016). It has been speculated that these characteristics indicate a symbiotic lifestyle, with energy acquired from hosts via ATP/ADP translocases, which has been confirmed experimentally in a few Dependentiae members (Delafont et al, 2015;Pagnier et al, 2015;Deeg et al, 2019). The well-characterized members of the bacterial phylum Tenericutes consist mostly of obligate pathogens with reduced genomes (Moran and Wernegreen, 2000).…”
Section: General Genome Featuresmentioning
confidence: 99%